2018
DOI: 10.4254/wjh.v10.i8.530
|View full text |Cite
|
Sign up to set email alerts
|

Current status of imaging in nonalcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common diffuse liver disease, with a worldwide prevalence of 20% to 46%. NAFLD can be subdivided into simple steatosis and nonalcoholic steatohepatitis. Most cases of simple steatosis are non-progressive, whereas nonalcoholic steatohepatitis may result in chronic liver injury and progressive fibrosis in a significant minority. Effective risk stratification and management of NAFLD requires evaluation of hepatic parenchymal fat, fibrosis, and inflammation. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
166
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(177 citation statements)
references
References 89 publications
3
166
0
8
Order By: Relevance
“…All our patients had ultrasound examinations for qualitative assessment of liver steatosis and it was found that a statistically significant difference regarding liver echogenicity detected by ultrasound as 83.33% of our patients in the second group had bright liver. This was in agreement with the study documented by Li et al, (2018) [37].…”
Section: Discussionsupporting
confidence: 94%
“…All our patients had ultrasound examinations for qualitative assessment of liver steatosis and it was found that a statistically significant difference regarding liver echogenicity detected by ultrasound as 83.33% of our patients in the second group had bright liver. This was in agreement with the study documented by Li et al, (2018) [37].…”
Section: Discussionsupporting
confidence: 94%
“…The spectrum of NAFLD ranges from simple steatosis to advanced stages, including nonalcoholic steatohepatitis (NASH), hepatic fibrosis, and cirrhosis . Different theories have been pointed out, leading initially to the “two‐hit hypothesis.” The first hit is insulin resistance (IR) and lipotoxicity causing hepatocyte injury, but a second hit is needed for chronic liver damage and includes apoptosis, oxidative stress, and lipid peroxidation . In patients with NAFLD, both environmental and genetic factors are involved in the insulin signaling pathway and therefore contribute to the maintenance and worsening of IR, inflammation, and fibrosis.…”
mentioning
confidence: 99%
“…CT parameters used to evaluate fatty liver include the absolute attenuation value (HULiver) and the attenuation value difference between the liver and spleen (HUL-S). An HUliver of 48 and a CTL-S of -2 are the threshold values for a 100% specific diagnosis of moderate-to-severe hepatic steatosis ( Figure 3) [28,29].…”
Section: Liver Steatosismentioning
confidence: 99%